Pengaruh Keselamatan dan Kesehatan Kerja terhadapKinerja Karyawan Bagian Pengecoran pada PT. XYZ - Putri, Manda Sari Nur Fadhilah; Khaerul Rizal Abdurahman (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of occupational safety and health on the performance of employees in the foundry department at PT. XYZ. The research method used was quantitative, with data collection techniques through interviews, observations, and questionnaires distributed to 35 foundry employees as respondents. The results showed that occupational safety and health, both partially and simultaneously, had a positive and significant effect on employee performance. The results of the multiple regression test obtained a coefficient of determination of 0.759, indicating that occupational safety and health influenced employee performance by 75.9%. The conclusion of this study is that the more optimal the implementation of occupational safety and health, the higher the employee performance demonstrated in achieving company goals.   Keywords: Occupational Safety, Occupational Health, Employee Performance, Personal Protective Equipment